Preliminary Study of WebGIS Implementation on Monitoring and Evaluation of the Regional Action Plan for Reduction and Elimination of Mercury Use (RAD-PPM) - Perbawati, Esti Kukuh; Purwanto, Taufik Hery; Petrus, Himawan Tri Bayu Murti; Santoso, Wahyu Yun (Universitas Muhammadiyah Surakarta, 2021)
Presidential Regulation Number 21 of 2019 concerning the National Action Plan for Mercury Reduction and Elimination (RAN-PPM) became the strategy for reduction and elimination of Mercury, then later revealed in the Regional Action Plan for Mercury Reduction and Elimination (RAD-PPM). According to it, a comprehensive monitoring method is urgently needed, neither only related to the elimination of mercury in the ASGM sector, but also for regional development potential. This research is a Research and Development research, which is a type of research that aims to develop applications, which are used as a tool for decision making-a Decision Support System (DSS). Using a descriptive qualitative method, to analyse related documents, interviews with related actors, and calculate System Usability Scale to analyse and see the usability and the level of user acceptance to the WebGIS. The case study is the development and preparation of a WebGIS related to the ASGM sector in Kokap, Kulon Progo. The result of the study shows that an information system with geospatial-based analysis could facilitate data integration, implementation and monitoring of the regulation of mercury elimination, especially in the ASGM sector. As a result of the WebGIS System Usability Scale for Small-Scale Gold Mining in Kulon Progo Regency, it is included in the category of applications that can be accepted by users and is quite appropriate. Nevertheless, synergy and cooperation between various agencies are necessary. Moreover, the data related to socio-economic which is an important information system for regional development can also be mapped in a GIS.